Preparation of degradable antibacterial fiber material
Through the preparation of silver nitrate and PVA/AGNO3 composite foam, combined with low -temperature primary solid -phase solid -phase and shell glycogenosilation technology to prepare a CA/CS/CNC fiber network coating with excellent antibacterial properties and good degradation, It solves the problem of incomparable materials between environmental protection, antibacterial and comfort.
Patent Information
- Application Number
- CN202411663782.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-28
AI Technical Summary
The existing degradable antibacterial fiber materials are difficult to balance between environmental protection, antibacteriality and comfort, and the preparation process is complex and the cost is high.
Preparation of silver nitrate, PVA/AGNO3 composite foam preparation, low temperature in original solid phase refretion of silver foam, chitosan spinning fiber, preparing for CS/CNC core fiber, and CA/CS/CNC fiber network coating Preparation has achieved efficient preparation of degradable antibacterial fiber materials.
This method not only improves the antibacterial properties and degradability of the material, but also optimizes the spinning technology, enhances the mechanical properties and comfort of the material, and reduces the preparation cost.
Smart Images

Figure CN119372807A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to preparation of a degradable antibacterial fiber material, belonging to the technical field of new materials. Background Art
[0002] As people's awareness of environmental protection and health increases, the demand for degradable antibacterial fiber materials is growing. This material not only has excellent antibacterial properties, but also can be quickly degraded in the natural environment, reducing environmental pollution. Therefore, the development of degradable antibacterial fiber materials has become a research hotspot in the current field of materials science.
[0003] Biodegradable antibacterial fiber materials have broad application prospects in the fields of medicine, hygiene, textiles, etc. For example, in the medical field, they can be used as wound dressings, surgical sutures, etc.; in the hygiene field, they can be used as antibacterial towels, antibacterial underwear, etc.; in the textile field, they can be used as antibacterial textiles, antibacterial bedding, etc. The development trend of degradable antibacterial fiber materials will pay more attention to the balance of environmental protection, antibacterial and comfort. On the one hand, it is necessary to continue to develop new bio-based polymer materials and antibacterial agents to improve the degradability and antibacterial effect of materials; on the other hand, it is necessary to optimize the spinning process and modification technology to improve the mechanical properties and comfort of materials. Summary of the invention
[0004] In view of the above problems, the present invention provides a method for preparing a degradable antibacterial fiber material.
[0005] The present invention provides a preparation method for a degradable antibacterial fiber material, comprising the following steps: step (1) preparing silver nitrate, step (2) preparing PVA / AgNO3 composite foam, step (3) preparing silver foam by low-temperature in-situ solid-phase reaction, step (4) preparing chitosan spinning solution, step (5) preparing chitosan microcapsules, step (6) preparing CS / CNC sheath-core fibers, and step (7) preparing the degradable antibacterial fiber material; Wherein, step (2) the preparation of PVA / AgNO3 composite foam comprises: PVA powder is poured into the AgNO3 solution prepared in step (1), stirred, and then placed in a sealed container to fully plasticize the solution; the plasticized particles are subjected to hot pressing to obtain PVA / AgNO3 composite sheets. The composite material obtained after the treatment is PVA / AgNO3-X, wherein X represents the proportion of AgNO3 in the total weight of PVA and AgNO3.
[0006] Preferably, step (1) silver nitrate is prepared Add analytical pure nitric acid HNO4 to distilled water for dilution, slowly add the crushed silver flakes to the diluted nitric acid, wait for it to slowly dissolve and then heat it up. After the yellow ammonia oxide disappears, evaporate and concentrate the dissolved supernatant until a white film appears on the surface of the container, then cool it to room temperature to obtain silver nitrate crystals; add the mixed solution containing the silver nitrate crystals to a suction filtration tank, vacuum filter, then wash with ice water, combine the filtrate and the washing water, and then concentrate and crystallize them again. The crystals are then dissolved in water and crystallized to obtain high-purity AgNO3; Step (2) Preparation of PVA / AgNO3 composite foam PVA powder is poured into the AgNO3 solution prepared in step (1), stirred, and then placed in a sealed container to fully plasticize the solution; the plasticized particles are subjected to hot pressing to obtain PVA / AgNO3 composite sheets, and the composite material obtained after the treatment is PVA / AgNO3-X, wherein X represents the proportion of AgNO3 in the total weight of PVA and AgNO3; in order to ensure that there is enough silver to form a network structure during the low-temperature in-situ solid-phase reaction stage and to prevent PVA from being over-plasticized and the melting decomposition temperature from being too low, the value of X is set within a certain range; Step (3) Preparation of silver foam by low-temperature in-situ solid phase reaction The PVA / AgNO3 composite foam prepared in step (2) is placed in a muffle furnace, and after heating, an in-situ solid phase reaction is induced to obtain a metallic silver foam; Step (4) Preparation of chitosan spinning solution Dissolve corn starch in distilled water and place in a high-pressure steam sterilizer to completely gelatinize it; cool the gelatinized starch, add pullulanase to perform enzymatic debranching, inactivate the enzyme, and cool to room temperature to obtain a debranched corn starch solution (DBS); add the silver foam prepared in step (3) and an acetic acid solution to obtain a chitosan spinning solution; Step (5) Chitosan microcapsule The chitosan spinning solution prepared in step (4) is added to folic acid, and sheared to obtain a wall core material suspension containing folic acid, and then spray-dried at the inlet to obtain chitosan-folic acid microcapsules; Step (6) Preparation of CS / CNC sheath-core fiber Connect a syringe containing chitosan solution to the outer diameter of the coaxial needle, connect a syringe containing CNCs suspension to the inner diameter of the needle, and place both syringes on a syringe pump, inject them into a coagulation bath and add the chitosan microcapsules prepared in step (5) to obtain CS / CNC skin-core fibers; the coagulation bath is a mixture of sodium hydroxide solution and ethanol; Step (7) Preparation of biodegradable antibacterial fiber material The CS / CNC sheath-core fiber prepared in step (6) is added, and CA is dissolved in a mixed solvent of acetone and deionized water to prepare a polymer / solvent / non-solvent precursor solution, and then the precursor solution is coated on the fabric using a blade coater, and then allowed to stand in a high humidity environment; the obtained hierarchical micro-nano porous CA / CS / CNC fiber network coating is placed in a vacuum oven to completely dry to remove acetone and water; after drying, it is peeled off to obtain an independent CA / CS / CNC coating.
[0007] Preferably, step (1) silver nitrate is prepared Analytical pure nitric acid HNO4 is diluted with distilled water 1-2 times at a ratio of 1-5:1-2, and the crushed silver flakes are slowly added to the diluted nitric acid at a ratio of liquid:solid=1-2.5:1-3, and dissolved at room temperature. After the dissolution is slow, the temperature is raised to 80-90°C. After the yellow ammonia oxide disappears, the dissolved supernatant is heated to 80-90°C, evaporated and concentrated until a white film appears on the surface of the container, and then cooled to room temperature to obtain silver nitrate crystals; the mixed solution containing the silver nitrate crystals is added to a suction filtration tank, vacuum filtered, and then washed with ice water 1-2 times to produce silver nitrate crystals with a purity greater than 90-99.8%; the filtrate and washing water are combined, concentrated and crystallized for a second time, and the crystals are then dissolved in water and crystallized to obtain AgNO3 with a purity of more than 90-99.5%.
[0008] The invention has the advantage that high-purity silver nitrate crystals can be prepared through multiple purifications such as raw material preparation and dilution, addition and dissolution of crushed coarse silver scraps, evaporation concentration, vacuum filtration, and ice water washing.
[0009] Preferably, step (2) PVA / AgNO3 composite foam preparation PVA powder is poured into the AgNO3 solution prepared in step (1), stirred for 10-15 minutes, and then placed in a sealed container and allowed to stand at 35-40°C for 40-48 hours to fully plasticize the solution; the plasticized particles are subjected to hot pressing to obtain PVA / AgNO3 composite sheets with a thickness of 2.0-4.0 mm; the molding temperature is 100-150°C and the molding pressure is 10-15.0 MPa; the obtained composite material is PVA / AgNO3-X, wherein X represents the proportion of AgNO3 in the total weight of PVA and AgNO3; in order to ensure that there is sufficient silver to form a network structure during the low-temperature in-situ solid-phase reaction stage and to prevent PVA from being over-plasticized and the melting decomposition temperature from being too low, the value of X is set to 10-50.
[0010] The advantages of the present invention are that PVA fully absorbs moisture and achieves the best plasticizing effect, while AgNO3 particles are evenly dispersed in the PVA matrix, which lays a good foundation for subsequent hot pressing treatment, is more conducive to efficient plasticizing, and ensures the stable distribution of AgNO3 particles in the PVA matrix. The optimized AgNO3 content not only ensures that the composite material has enough silver to form a network structure in the low-temperature in-situ solid-phase reaction stage, but also prevents the problems of excessive plasticization of PVA and too low melting decomposition temperature, thereby enhancing the stability and durability of the material.
[0011] Preferably, step (3) is to prepare silver foam by low temperature in-situ solid phase reaction The PVA / AgNO3 composite foam prepared in step (2) is placed in a muffle furnace and heated to 160-210°C at a heating rate of 1-5°C / min to induce an in-situ solid phase reaction to obtain metallic silver foam.
[0012] The advantages of the present invention are that the relatively low temperature helps to reduce energy consumption and cost, and the PVA molecular chain can undergo dehydration reaction and breakage to produce various unsaturated structures, thereby reducing silver ions to form metallic silver foam. This process is efficient and controllable. During the in situ solid phase reaction, Ag + It is reduced to elemental silver by PVA. This reduction process occurs in the pores of the PVA / AgNO3 composite foam, allowing the silver particles to self-assemble along the foam structure to form a three-dimensional open-pore metallic silver foam. This self-assembly process gives the silver foam excellent structural properties and catalytic properties.
[0013] Preferably, in step (4), preparation of chitosan spinning solution Dissolve 10-15 g corn starch in 90-100 mL distilled water, place in a 100-121° C. high pressure steam sterilizer for 15-20 min to completely gelatinize it; cool the gelatinized starch to 50-58° C., add 180-200 μL pullulanase for enzymatic debranching for 1-5 h, inactivate the enzyme, and cool to room temperature to obtain a debranched corn starch solution (DBS); add the silver foam prepared in step (3), and add 1-3% acetic acid solution to prepare a chitosan spinning solution with a mass fraction of 0-2%.
[0014] The advantage of the present invention is that debranched corn starch solution (DBS) is combined with silver foam and chitosan spinning solution to prepare chitosan spinning solution with unique properties, which integrates polysaccharide materials, metal foam and enzyme engineering technology. The addition of silver foam gives the chitosan spinning solution excellent antibacterial properties.
[0015] Preferably, in step (5), chitosan microcapsules The chitosan spinning solution prepared in step (4) is added to folic acid, and sheared at 6000-6500 r / min for 15-30 min to obtain a wall core material suspension containing 0.5-2% folic acid, and then spray-dried at an inlet temperature of 150-200°C and a flow rate of 1-4 mL / min to obtain chitosan-folic acid microcapsules.
[0016] Preferably, step (6) preparation of CS / CNC sheath-core fiber A 10-15 mL syringe filled with 2.0-2.5% chitosan solution is connected to the outer diameter of a coaxial needle (needle inner diameter 0.30-0.50 mm, needle outer diameter 1.20-1.26 mm), a 1-5 mL syringe filled with CNCs suspension (0-4%) is connected to the inner diameter of the needle, and both syringes are placed on a syringe pump, injected into a coagulation bath at a flow rate of 0.6-0.8 mL / min and the chitosan microcapsules prepared in step (5) are added to obtain CS / CNC skin-core fibers; the coagulation bath is a mixture of 1-5% sodium hydroxide solution and ethanol, wherein the mass ratio of sodium hydroxide solution to ethanol is 3-6:2-4.
[0017] The present invention has the advantage that the chitosan solution and the CNCs suspension are simultaneously injected into the coagulation bath through a coaxial needle, thereby realizing the precise construction of the skin-core structure. This technology not only improves the preparation efficiency of the fiber, but also ensures the uniformity and stability of the skin-core structure. CS / CNC sheath-core fiber has a unique double-layer structure, with the sheath being chitosan and the core being CNCs. This structure allows the fiber to maintain the excellent properties of chitosan while also having the high strength and high modulus of CNCs, thus giving the fiber more excellent comprehensive performance.
[0018] Preferably, step (7) preparation of degradable antibacterial fiber material The CS / CNC sheath-core fiber prepared in step (6) is added, and CA is dissolved in a mixed solvent of acetone and deionized water to prepare a polymer / solvent / non-solvent precursor solution; the precursor solution is then coated on the fabric using a blade coater, and then allowed to stand for 1-5 hours at room temperature of 20-25°C and a high humidity environment of 90-95%; the obtained hierarchical micro-nano porous CA / CS / CNC fiber network coating is placed in a vacuum oven to completely dry to remove acetone and water; after drying, an independent CA / CS / CNC coating is peeled off, and the coating maintains the same thickness, the coating on the fabric is about 45-50µm, and the independent coating is about 95-100µm.
[0019] The advantage of the present invention is that by combining CS / CNC sheath-core fiber with CA (cellulose acetate), the prepared degradable antibacterial fiber material not only inherits the excellent properties of chitosan and cellulose nanocrystals (CNCs), such as biocompatibility and degradability, but also has good antibacterial properties; chitosan and CNCs themselves have certain antibacterial activity, and the addition of CA further enhances the antibacterial properties of the material.
[0020] In summary, the present invention has the following beneficial effects: 1. The present invention has the advantage that high-purity silver nitrate crystals can be prepared through multiple purifications such as raw material preparation and dilution, addition and dissolution of crushed coarse silver scraps, evaporation concentration, vacuum filtration, and ice water washing; 2. The present invention has the advantages that PVA fully absorbs water and achieves the best plasticizing effect, while AgNO3 particles are evenly dispersed in the PVA matrix, which lays a good foundation for subsequent hot pressing treatment, is more conducive to efficient plasticization, and ensures the stable distribution of AgNO3 particles in the PVA matrix. The optimized AgNO3 content not only ensures that the composite material has enough silver to form a network structure in the low-temperature in-situ solid-phase reaction stage, but also prevents the problem of excessive plasticization of PVA and too low melting decomposition temperature, thereby enhancing the stability and durability of the material; 3. The present invention has the advantages that relatively low temperature helps to reduce energy consumption and cost. The PVA molecular chain can undergo dehydration reaction and breakage to produce various unsaturated structures, thereby reducing silver ions to form metallic silver foam. This process is efficient and controllable. In the in-situ solid phase reaction process, Ag + It is reduced to elemental silver by PVA. This reduction process occurs in the pores of the PVA / AgNO3 composite foam, allowing the silver particles to self-assemble along the foam structure to form a three-dimensional open-cell metallic silver foam. This self-assembly process gives the silver foam excellent structural properties and catalytic properties. 4. The present invention has the advantages that debranched corn starch solution (DBS) is combined with silver foam and chitosan spinning solution to prepare chitosan spinning solution with unique properties, which integrates polysaccharide materials, metal foam and enzyme engineering technology. The addition of silver foam gives the chitosan spinning solution excellent antibacterial properties; 5. The present invention has the advantage that the chitosan solution and the CNCs suspension are simultaneously injected into the coagulation bath through a coaxial needle, thereby realizing the precise construction of the skin-core structure. This technology not only improves the preparation efficiency of the fiber, but also ensures the uniformity and stability of the skin-core structure. The CS / CNC skin-core fiber has a unique double-layer structure, with the skin layer being chitosan and the core layer being CNCs. This structure enables the fiber to have the high strength, high modulus and other characteristics of CNCs while maintaining the excellent properties of chitosan, thereby giving the fiber more excellent comprehensive performance; 6. The advantage of the present invention is that by combining CS / CNC core-skin fiber with CA (cellulose acetate), the prepared degradable antibacterial fiber material not only inherits the excellent properties of chitosan and cellulose nanocrystals (CNCs), such as biocompatibility and degradability, but also has good antibacterial properties; chitosan and CNCs themselves have certain antibacterial activity, and the addition of CA further enhances the antibacterial properties of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The present invention is a flow chart for preparing a degradable antibacterial fiber material. DETAILED DESCRIPTION
[0022] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.
[0023] If not specifically stated, the technical means used in the examples are conventional means known to those skilled in the art. In addition, all the raw materials used in the examples are known commercial products.
[0024] Example 1 Step (1) Preparation of silver nitrate Analytical pure nitric acid HNO4 is diluted with distilled water at a ratio of 1:1. The crushed silver flakes are slowly added to the diluted nitric acid at a ratio of liquid:solid = 1:1, dissolved at room temperature, and then heated to 82°C after the dissolution is slow. After the yellow ammonia oxide disappears, the dissolved supernatant is heated to 83°C, evaporated and concentrated until a white film appears on the surface of the container, and then cooled to room temperature to obtain silver nitrate crystals; the mixed solution containing the silver nitrate crystals is added to the suction filtration tank, vacuum filtered, and then washed with ice water once to produce silver nitrate crystals with a purity greater than 92%; the filtrate and washing water are combined, concentrated and crystallized for a second time, and the crystals are then dissolved in water and crystallized to obtain AgNO3 with a purity of more than 92%; Step (2) Preparation of PVA / AgNO3 composite foam PVA powder is poured into the AgNO3 solution prepared in step (1), stirred for 10 minutes, and then placed in a sealed container and allowed to stand at 35°C for 40 hours to fully plasticize the solution; the plasticized particles are subjected to hot pressing to obtain PVA / AgNO3 composite sheets with a thickness of 2.0 mm; the molding temperature is 100°C and the molding pressure is 10 MPa; the obtained composite material is PVA / AgNO3-X, wherein X represents the proportion of AgNO3 in the total weight of PVA and AgNO3; in order to ensure that there is enough silver to form a network structure during the low-temperature in-situ solid-phase reaction stage and to prevent PVA from being over-plasticized and the melting decomposition temperature from being too low, the value of X is set to 12; Step (3) Preparation of silver foam by low-temperature in-situ solid phase reaction The PVA / AgNO3 composite foam prepared in step (2) is placed in a muffle furnace and heated to 160°C at a heating rate of 1°C / min to induce an in-situ solid phase reaction to obtain a metallic silver foam; Step (4) Preparation of chitosan spinning solution Dissolve 12 g corn starch in 95 mL distilled water, place in a 100° C. high-pressure steam sterilizer for 15 min to completely gelatinize it; cool the gelatinized starch to 50° C., add 180 μL of pullulanase for enzymatic debranching for 1 h, inactivate the enzyme, and cool to room temperature to obtain a debranched corn starch solution (DBS); add the silver foam prepared in step (3), and add 1% acetic acid solution to prepare a chitosan spinning solution with a mass fraction of 1%; Step (5) Chitosan microcapsule The chitosan spinning solution prepared in step (4) was added to folic acid, and sheared at 6000 r / min for 15 min to obtain a wall core material suspension containing 0.5% folic acid, and then spray-dried at an inlet temperature of 150°C and a flow rate of 1 mL / min to obtain chitosan-folic acid microcapsules; Step (6) Preparation of CS / CNC sheath-core fiber A 10 mL syringe filled with 2.0% chitosan solution was connected to the outer diameter of a coaxial needle (needle inner diameter 0.30 mm, needle outer diameter 1.20 mm), and a 1 mL syringe filled with CNCs suspension (1%) was connected to the inner diameter of the needle, and both syringes were placed on a syringe pump, injected into a coagulation bath at a flow rate of 0.6 mL / min and added with the chitosan microcapsules prepared in step (5), to obtain CS / CNC skin-core fibers; the coagulation bath was prepared by mixing 1% sodium hydroxide solution and ethanol, wherein the mass ratio of sodium hydroxide solution to ethanol was 3:2; Step (7) Preparation of biodegradable antibacterial fiber material The CS / CNC sheath-core fiber prepared in step (6) was added, and CA was dissolved in a mixed solvent of acetone and deionized water to prepare a polymer / solvent / non-solvent precursor solution with a mass ratio of 0.5:7.1:1.1; the precursor solution was then coated on different fabrics using a blade coater, and then allowed to stand at room temperature of 20°C and a high humidity environment of 90% for 1 hour; the obtained hierarchical micro-nano porous CA / CS / CNC fiber network coating was placed in a vacuum oven to completely dry to remove acetone and water. ; At the same time, a CA / CS / CNC acetone (mass ratio of 1.1:8.0) precursor solution was prepared without adding deionized water. In an oven at 45°C, a non-porous CA / CS / CNC coating was prepared using the CA / CS / CNC acetone (mass ratio of 1.1:8.0) precursor solution without the influence of air moisture. After drying, the independent CA / CS / CNC coating was peeled off. All coatings could be maintained at the same thickness, with the coating on the fabric being approximately 45µm and the independent coating being approximately 95µm.
[0025] Example 2 Step (1) Preparation of silver nitrate Analytical pure nitric acid HNO4 is diluted with distilled water twice at a ratio of 2:1. The crushed silver flakes are slowly added to the diluted nitric acid at a ratio of liquid:solid=2.5:1, dissolved at room temperature, and then heated to 85°C after the dissolution is slow. After the yellow ammonia oxide disappears, the dissolved supernatant is heated to 85°C, evaporated and concentrated until a white film appears on the surface of the container, and then cooled to room temperature to obtain silver nitrate crystals; the mixed solution containing the silver nitrate crystals is added to the suction filtration tank, vacuum filtered, and then washed once with ice water to produce silver nitrate crystals with a purity greater than 95%; the filtrate and washing water are combined, concentrated and crystallized twice, and the crystals are then dissolved in water and crystallized to obtain AgNO3 with a purity of more than 95%; Step (2) Preparation of PVA / AgNO3 composite foam PVA powder is poured into the AgNO3 solution prepared in step (1), stirred for 10 minutes, and then placed in a sealed container and allowed to stand at 36°C for 42 hours to fully plasticize the solution; the plasticized particles are subjected to hot pressing to obtain PVA / AgNO3 composite sheets with a thickness of 3.0 mm; the molding temperature is 100°C and the molding pressure is 12 MPa; the obtained composite material is PVA / AgNO3-X, wherein X represents the proportion of AgNO3 in the total weight of PVA and AgNO3; in order to ensure that there is enough silver to form a network structure during the low-temperature in-situ solid-phase reaction stage and to prevent PVA from being over-plasticized and the melting decomposition temperature from being too low, the value of X is set to 15; Step (3) Preparation of silver foam by low-temperature in-situ solid phase reaction The PVA / AgNO3 composite foam prepared in step (2) is placed in a muffle furnace and heated to 170°C at a heating rate of 2°C / min to induce an in-situ solid phase reaction to obtain a metallic silver foam; Step (4) Preparation of chitosan spinning solution Dissolve 13 g corn starch in 95 mL distilled water, place in a 110° C. high-pressure steam sterilizer for 15 min to completely gelatinize; cool the gelatinized starch to 52° C., add 185 μL pullulanase for enzymatic debranching for 2 h, inactivate the enzyme, and cool to room temperature to obtain a debranched corn starch solution (DBS); add the silver foam prepared in step (3), and add 2% acetic acid solution to prepare a chitosan spinning solution with a mass fraction of 1%; Step (5) Chitosan microcapsule The chitosan spinning solution prepared in step (4) was added to folic acid, and sheared at 6100 r / min for 20 min to obtain a wall core material suspension containing 0.5% folic acid, and then spray-dried at an inlet temperature of 160°C and a flow rate of 2 mL / min to obtain chitosan-folic acid microcapsules; Step (6) Preparation of CS / CNC sheath-core fiber A 13 mL syringe filled with 2.0% chitosan solution was connected to the outer diameter of a coaxial needle (needle inner diameter 0.40 mm, needle outer diameter 1.23 mm), and a 3 mL syringe filled with CNCs suspension (2%) was connected to the inner diameter of the needle. Both syringes were placed on a syringe pump, and injected into a coagulation bath at a flow rate of 0.7 mL / min and the chitosan microcapsules prepared in step (5) were added to obtain CS / CNC skin-core fibers; the coagulation bath was prepared by mixing 2% sodium hydroxide solution and ethanol, wherein the mass ratio of sodium hydroxide solution to ethanol was 5:2; Step (7) Preparation of biodegradable antibacterial fiber material The CS / CNC sheath-core fiber prepared in step (6) is added, and CA is dissolved in a mixed solvent of acetone and deionized water to prepare a polymer / solvent / non-solvent precursor solution; the precursor solution is then coated on the fabric using a blade coater, and then allowed to stand for 2 hours at room temperature of 22°C and a high humidity environment of 92%; the obtained hierarchical micro-nano porous CA / CS / CNC fiber network coating is placed in a vacuum oven to completely dry to remove acetone and water; after drying, an independent CA / CS / CNC coating is peeled off, and the coating maintains the same thickness, the coating on the fabric is about 45µm, and the independent coating is about 96µm.
[0026] Example 3 Step (1) Preparation of silver nitrate Analytical pure nitric acid HNO4 is diluted with distilled water twice at a ratio of 1:2, and the crushed silver flakes are slowly added to the diluted nitric acid at a ratio of liquid:solid=2.5:3, and dissolved at room temperature. After the solution slowly dissolves, the temperature is raised to 90°C. After the yellow ammonia oxide disappears, the dissolved supernatant is heated to 90°C, evaporated and concentrated until a white film appears on the surface of the container, and then cooled to room temperature to obtain silver nitrate crystals; the mixed solution containing the silver nitrate crystals is added to the suction filtration tank, vacuum filtered, and then washed twice with ice water to produce silver nitrate crystals with a purity greater than 97.5%; the filtrate and washing water are combined, concentrated and crystallized twice, and the crystals are then dissolved in water and crystallized to obtain AgNO3 with a purity of more than 97.5%; Step (2) Preparation of PVA / AgNO3 composite foam PVA powder is poured into the AgNO3 solution prepared in step (1), stirred for 15 minutes, and then placed in a sealed container and allowed to stand at 40°C for 48 hours to fully plasticize the solution; the plasticized particles are subjected to hot pressing to obtain PVA / AgNO3 composite sheets with a thickness of 4.0 mm; the molding temperature is 150°C and the molding pressure is 15.0 MPa; the obtained composite material is PVA / AgNO3-X, wherein X represents the proportion of AgNO3 in the total weight of PVA and AgNO3; in order to ensure that there is enough silver to form a network structure during the low-temperature in-situ solid-phase reaction stage and to prevent PVA from being over-plasticized and the melting decomposition temperature from being too low, the value of X is set to 45; Step (3) Preparation of silver foam by low-temperature in-situ solid phase reaction The PVA / AgNO3 composite foam prepared in step (2) is placed in a muffle furnace and heated to 210°C at a heating rate of 4°C / min to induce an in-situ solid phase reaction to obtain a metallic silver foam; Step (4) Preparation of chitosan spinning solution Dissolve 14 g corn starch in 95 mL distilled water, place in a 120° C. high-pressure steam sterilizer for 18 min to completely gelatinize; cool the gelatinized starch to 57° C., add 190 μL pullulanase for enzymatic debranching for 1 h, inactivate the enzyme, and cool to room temperature to obtain a debranched corn starch solution (DBS); add the silver foam prepared in step (3), and add 2% acetic acid solution to prepare a chitosan spinning solution with a mass fraction of 2%; Step (5) Chitosan microcapsule The chitosan spinning solution prepared in step (4) was added to folic acid, and sheared at 6400 r / min for 15 min to obtain a wall core material suspension containing 1% folic acid, and then spray-dried at an inlet temperature of 180°C and a flow rate of 3 mL / min to obtain chitosan-folic acid microcapsules; Step (6) Preparation of CS / CNC sheath-core fiber A 14 mL syringe filled with 2.0% chitosan solution was connected to the outer diameter of a coaxial needle (needle inner diameter 0.40 mm, needle outer diameter 1.22 mm), and a 2 mL syringe filled with CNCs suspension (2%) was connected to the inner diameter of the needle, and both syringes were placed on a syringe pump, injected into a coagulation bath at a flow rate of 0.7 mL / min and added with the chitosan microcapsules prepared in step (5), to obtain CS / CNC skin-core fibers; the coagulation bath was prepared by mixing 4% sodium hydroxide solution and ethanol, wherein the mass ratio of sodium hydroxide solution to ethanol was 3:2; Step (7) Preparation of biodegradable antibacterial fiber material The CS / CNC sheath-core fiber prepared in step (6) is added, and CA is dissolved in a mixed solvent of acetone and deionized water to prepare a polymer / solvent / non-solvent precursor solution; the precursor solution is then coated on the fabric using a doctor blade coater, and then allowed to stand for 2 hours at room temperature of 22°C and a high humidity environment of 94%; the obtained hierarchical micro-nano porous CA / CS / CNC fiber network coating is placed in a vacuum oven to completely dry to remove acetone and water; after drying, an independent CA / CS / CNC coating is peeled off, and the coating maintains the same thickness, the coating on the fabric is about 48µm, and the independent coating is about 100µm.
[0027] Example 4 Step (1) Preparation of silver nitrate Analytical pure nitric acid HNO4 is diluted with distilled water at a ratio of 1:1, and the crushed silver flakes are slowly added to the diluted nitric acid at a ratio of liquid:solid=1.5:1, and dissolved at room temperature. After the solution slowly dissolves, the temperature is raised to 90°C. After the yellow ammonia oxide disappears, the dissolved supernatant is heated to 90°C, evaporated and concentrated until a white film appears on the surface of the container, and then cooled to room temperature to obtain silver nitrate crystals; the mixed solution containing the silver nitrate crystals is added to the suction filtration tank, vacuum filtered, and then washed with ice water twice to produce silver nitrate crystals with a purity greater than 99.8%; the filtrate and washing water are combined, concentrated and crystallized for a second time, and the crystals are then dissolved in water and crystallized to obtain AgNO3 with a purity of more than 99.5%; Step (2) Preparation of PVA / AgNO3 composite foam PVA powder is poured into the AgNO3 solution prepared in step (1), stirred for 10 minutes, and then placed in a sealed container and allowed to stand at 40°C for 48 hours to fully plasticize the solution; the plasticized particles are subjected to hot pressing to obtain PVA / AgNO3 composite sheets with a thickness of 2.0 mm; the molding temperature is 150°C and the molding pressure is 15.0 MPa; the obtained composite material is PVA / AgNO3-X, wherein X represents the proportion of AgNO3 in the total weight of PVA and AgNO3; in order to ensure that there is enough silver to form a network structure during the low-temperature in-situ solid-phase reaction stage and to prevent PVA from being over-plasticized and the melting decomposition temperature from being too low, the value of X is set to 50; Step (3) Preparation of silver foam by low-temperature in-situ solid phase reaction The PVA / AgNO3 composite foam prepared in step (2) is placed in a muffle furnace and heated to 210°C at a heating rate of 5°C / min to induce an in-situ solid phase reaction to obtain a metallic silver foam; Step (4) Preparation of chitosan spinning solution Dissolve 10 g corn starch in 100 mL distilled water, place in a 121° C. high-pressure steam sterilizer for 20 min to completely gelatinize it; cool the gelatinized starch to 58° C., add 200 μL pullulanase for enzymatic debranching for 5 h, inactivate the enzyme, and cool to room temperature to obtain a debranched corn starch solution (DBS); add the silver foam prepared in step (3), and add 1% acetic acid solution to prepare a chitosan spinning solution with a mass fraction of 2%; Step (5) Chitosan microcapsule The chitosan spinning solution prepared in step (4) was added to folic acid, and sheared at 6500 r / min for 15 min to obtain a wall core material suspension containing 0.5% folic acid, and then spray-dried at an inlet temperature of 150°C and a flow rate of 4 mL / min to obtain chitosan-folic acid microcapsules; Step (6) Preparation of CS / CNC sheath-core fiber A 10 mL syringe filled with 2.5% chitosan solution was connected to the outer diameter of a coaxial needle (needle inner diameter 0.50 mm, needle outer diameter 1.26 mm), and a 5 mL syringe filled with CNCs suspension (4%) was connected to the inner diameter of the needle. Both syringes were placed on a syringe pump, injected into a coagulation bath at a flow rate of 0.8 mL / min and the chitosan microcapsules prepared in step (5) were added to obtain CS / CNC skin-core fibers; the coagulation bath was a mixture of 5% sodium hydroxide solution and ethanol, wherein the mass ratio of sodium hydroxide solution to ethanol was 6:4.
[0028] Step (7) Preparation of biodegradable antibacterial fiber material The CS / CNC sheath-core fiber prepared in step (6) is added, and CA is dissolved in a mixed solvent of acetone and deionized water to prepare a polymer / solvent / non-solvent precursor solution, and then the precursor solution is coated on the fabric using a doctor blade coater, and then allowed to stand for 1 hour at room temperature of 25°C and a high humidity environment of 90%; the obtained hierarchical micro-nano porous CA / CS / CNC fiber network coating is placed in a vacuum oven to completely dry to remove acetone and water; after drying, an independent CA / CS / CNC coating can be obtained by peeling it off, and the coating maintains the same thickness, the coating on the fabric is about 50µm, and the independent coating is about 100µm.
[0029] Comparative Example 1 Step (1) Preparation of silver nitrate Analytical pure nitric acid HNO4 is diluted with distilled water three times at a ratio of 5:7, and the crushed silver flakes are slowly added to the diluted nitric acid at a ratio of liquid:solid=2.5:1, and dissolved at room temperature. After the solution slowly dissolves, the temperature is raised to 95°C. After the yellow ammonia oxide disappears, the dissolved supernatant is heated to 95°C, evaporated and concentrated until a white film appears on the surface of the container, and then cooled to room temperature to obtain silver nitrate crystals; the mixed solution containing the silver nitrate crystals is added to the suction filtration tank, vacuum filtered, and then washed with ice water three times to produce silver nitrate crystals with a purity greater than 89%; the filtrate and washing water are combined, concentrated and crystallized for a second time, and the crystals are then dissolved in water and crystallized to obtain AgNO3 with a purity of more than 85%; Step (2) Preparation of PVA / AgNO3 composite foam PVA powder is poured into the AgNO3 solution prepared in step (1), stirred for 30 minutes, and then placed in a sealed container and allowed to stand at 50°C for 48 hours to fully plasticize the solution; the plasticized particles are subjected to hot pressing to obtain a PVA / AgNO3 composite sheet with a thickness of 5.0 mm; the molding temperature is 160°C and the molding pressure is 16.0 MPa; the obtained composite material is PVA / AgNO3-X, wherein X represents the proportion of AgNO3 in the total weight of PVA and AgNO3; in order to ensure that there is enough silver to form a network structure during the low-temperature in-situ solid-phase reaction stage and to prevent PVA from being over-plasticized and the melting decomposition temperature from being too low, the value of X is set to 50; Step (3) Preparation of silver foam by low-temperature in-situ solid phase reaction The PVA / AgNO3 composite foam prepared in step (2) is placed in a muffle furnace and heated to 220°C at a heating rate of 6°C / min to induce an in-situ solid phase reaction to obtain a metallic silver foam; Step (4) Preparation of chitosan spinning solution Dissolve 20 g corn starch in 150 mL distilled water, place in a 125° C. high-pressure steam sterilizer for 30 min to completely gelatinize; cool the gelatinized starch to 60° C., add 200 μL pullulanase for enzymatic debranching for 6 h, inactivate the enzyme, and cool to room temperature to obtain a debranched corn starch solution (DBS); add the silver foam prepared in step (3), and add 5% acetic acid solution to prepare a chitosan spinning solution with a mass fraction of 5%; Step (5) Preparation of CS / CNC sheath-core fiber A 20 mL syringe filled with 3.5% chitosan spinning solution prepared in step (4) was connected to the outer diameter of a coaxial needle (needle inner diameter 0.50 mm, needle outer diameter 1.26 mm), and a 6 mL syringe filled with CNCs suspension (4%) was connected to the inner diameter of the needle. Both syringes were placed on a syringe pump and injected into a coagulation bath at a flow rate of 0.8 mL / min to obtain CS / CNC skin-core fibers; the coagulation bath was prepared by mixing 5% sodium hydroxide solution and ethanol, wherein the mass ratio of sodium hydroxide solution to ethanol was 3:2; Step (6) Preparation of biodegradable antibacterial fiber material The CS / CNC sheath-core fiber prepared in step (5) was added, and CA was dissolved in a mixed solvent of acetone and deionized water to prepare a polymer / solvent / non-solvent precursor solution with a mass ratio of 1.1:7.8:2.2; the precursor solution was then coated on different fabrics using a blade coater, and then allowed to stand at room temperature of 25°C and a high humidity environment of 98% for 6 hours; the obtained hierarchical micro-nano porous CA / CS / CNC fiber network coating was placed in a vacuum oven to completely dry to remove acetone and water. ; At the same time, a CA / CS / CNC acetone (mass ratio of 2.2:8.9) precursor solution was prepared without adding deionized water. In an oven at 60°C, a non-porous CA / CS / CNC coating was prepared using the CA / CS / CNC acetone (mass ratio of 2.2:8.9) precursor solution without the influence of air moisture. After drying, the independent CA / CS / CNC coating was peeled off. All coatings could be maintained at the same thickness, with the coating on the fabric being approximately 50µm and the independent coating being approximately 100µm.
[0030] Comparative Example 2 Step (1) Preparation of silver nitrate Analytical pure nitric acid HNO4 is diluted with distilled water at a ratio of 2:1, and the crushed silver flakes are slowly added to the diluted nitric acid at a ratio of liquid:solid = 1:1, and dissolved at room temperature. After the solution slowly dissolves, the temperature is raised to 75°C. After the yellow ammonia oxide disappears, the dissolved supernatant is heated to 75°C, evaporated and concentrated until a white film appears on the surface of the container, and then cooled to room temperature to obtain silver nitrate crystals; the mixed solution containing the silver nitrate crystals is added to the suction filtration tank, vacuum filtered, and then washed with ice water once to produce silver nitrate crystals with a purity greater than 88%; the filtrate and washing water are combined, concentrated and crystallized for a second time, and the crystals are then dissolved in water and crystallized to obtain AgNO3 with a purity of more than 88%; Step (2) Preparation of super-critical PVA / AgNO3 composite foam PVA powder is poured into the AgNO3 solution prepared in step (1), stirred for 5 minutes, and then placed in a sealed container and allowed to stand at 25°C for 30 hours to fully plasticize the solution; the plasticized particles are subjected to hot pressing to obtain PVA / AgNO3 composite sheets with a thickness of 2.0 mm; the molding temperature is 95°C and the molding pressure is 10 MPa; the obtained composite material is PVA / AgNO3-X, wherein X represents the proportion of AgNO3 in the total weight of PVA and AgNO3; in order to ensure that there is enough silver to form a network structure during the low-temperature in-situ solid-phase reaction stage and to prevent PVA from being over-plasticized and the melting decomposition temperature from being too low, the value of X is set to 15; Step (3) Preparation of silver foam by low-temperature in-situ solid phase reaction The PVA / AgNO3 composite foam prepared in step (2) is placed in a muffle furnace and heated to 150°C at a heating rate of 1°C / min to induce an in-situ solid phase reaction to obtain a metallic silver foam; Step (4) Preparation of chitosan spinning solution Dissolve 5 g corn starch in 85 mL distilled water and place in a 100° C. high-pressure steam sterilizer for 10 min to completely gelatinize it; cool the gelatinized starch to 45° C., add 175 μL pullulanase for enzymatic debranching for 4 h, inactivate the enzyme, and cool to room temperature to obtain a debranched corn starch solution (DBS); add the silver foam prepared in step (3), and add 2% acetic acid solution to prepare a chitosan spinning solution with a mass fraction of 22%; Step (5) Chitosan microcapsule The chitosan spinning solution prepared in step (4) was added to folic acid, and sheared at 5500 r / min for 10 min to obtain a wall core material suspension containing 0.5% folic acid, and then spray-dried at an inlet temperature of 130°C and a flow rate of 1 mL / min to obtain chitosan-folic acid microcapsules; Step (6) Preparation of biodegradable antibacterial fiber material The CS / CNC sheath-core fiber prepared in step (5) was added, and CA was dissolved in a mixed solvent of acetone and deionized water to prepare a polymer / solvent / non-solvent precursor solution with a mass ratio of 0.5:7.1:1.1; the precursor solution was then coated on different fabrics using a blade coater, and then allowed to stand at room temperature of 22°C and a high humidity environment of 92% for 2 hours; the obtained hierarchical micro-nano porous CA / CS / CNC fiber network coating was placed in a vacuum oven to completely dry to remove acetone and water; at the same time, a CA / CS / CNC acetone (mass ratio of 1.1:8.0) precursor solution was prepared without adding deionized water. In an oven at 40°C, a CA / CS / CNC acetone (mass ratio of 1.1:8.0) precursor solution was used to prepare a non-porous CA / CS / CNC coating without the influence of air moisture. After drying, the independent CA / CS / CNC coating was peeled off. All coatings could be maintained at the same thickness, the coating on the fabric was about 40µm, and the independent coating was about 95µm.
[0031] Comparison of detection experiments: The degradable antibacterial fiber materials obtained in Examples 1 to 4 and Comparative Example Products 1 and 2 were tested. The specific testing methods are as follows: Antibacterial performance test The bacterial solution is added to the surface of the sample and covered with a layer of plastic film to make the bacterial solution evenly distributed on the sample surface. The sample is cultured in an environment with a humidity greater than 90%. After the culture, the sample is eluted and the colony counted. The colony of the sample is compared with that of the blank sample to calculate the antibacterial rate of the sample.
[0032] Degradability test Evaluate the degradation performance of materials in natural environment or specific conditions, prepare samples according to test requirements, and ensure the representativeness and consistency of samples. Select appropriate microorganisms, such as bacteria, fungi, etc., according to the type of material and the expected degradation environment; culture medium: provide nutrients required for microbial growth, such as carbon source, nitrogen source, inorganic salts, etc. Temperature: usually between 20-37℃, humidity: maintain a humidity level of 30%-80% to ensure the normal growth of microorganisms and sufficient wetting of materials.
[0033] Determination of metal ion content To ensure the accuracy of the concentration and volume of the solution by using the reaction between silver ions and acid, prepare 100mL of 0.01mol / L silver ion solution, select 0.1mol / L hydrochloric acid solution, and use it for titration after calibration; carry out at room temperature, usually controlled between 20-25℃, and maintain 1-2 drops per second to reduce the influence of temperature on the titration reaction.
[0034] Table 1 Antibacterial performance test
[0035] As can be seen from Table 1, Example 4 is the best, while Comparative Example 2 is relatively poor. Example 4 has the best antibacterial performance. In Example 4, the purity of silver nitrate reaches 99.8%, while in Comparative Example 2 it is only 88%. High-purity silver nitrate means that more and purer silver particles can be generated in subsequent reactions, thereby enhancing the antibacterial effect; the low-temperature in-situ solid phase reaction in Example 4 has a faster heating rate and a higher temperature, which helps to accelerate the generation and aggregation of silver particles, forming a denser and more uniform silver foam structure, and significantly improving the antibacterial performance; the degradable antibacterial fiber material in Example 4 has better antibacterial effect, stability and durability.
[0036] Table 2 Degradability test
[0037] As can be seen from Table 2, Example 4 is the best, while Comparative Example 2 is relatively poor. Since the materials in Example 4 use natural high molecular substances, such as chitosan, cellulose nanocrystals and degradable polymer cellulose acetate, these materials have good degradation performance in the natural environment. The design and optimization of the material structure also help to improve the degradation rate and degree in the natural environment. In contrast, the materials in Comparative Example 2 are not as good as Example 4 in degradation performance in the natural environment due to differences in preparation process and structural design.
[0038] Table 3 Determination of metal ion content
[0039] As can be seen from Table 3, Example 4 is the best and Comparative Example 1 is the worst. Since the purity of silver nitrate in Example 4 is higher, more and purer metallic silver can be generated in the subsequent preparation of PVA / AgNO3 composite foam and the preparation of silver foam by low-temperature in-situ solid phase reaction; while in Comparative Example 1, due to the lower purity of silver nitrate, the generated metallic silver content is reduced or contains more impurities.
[0040] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed, but they are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A preparation method for a degradable antibacterial fiber material, characterized in that: include: Step (1) preparation of silver nitrate, step (2) preparation of PVA / AgNO3 composite foam, step (3) preparation of silver foam by low-temperature in-situ solid phase reaction, step (4) preparation of chitosan spinning solution, step (5) preparation of chitosan microcapsules, step (6) preparation of CS / CNC sheath-core fibers, and step (7) preparation of degradable antibacterial fiber materials; Wherein, step (2) the preparation of PVA / AgNO3 composite foam comprises: PVA powder is poured into the AgNO3 solution prepared in step (1), stirred, and then placed in a sealed container to fully plasticize the solution; the plasticized particles are subjected to hot pressing to obtain PVA / AgNO3 composite sheets. The composite material obtained after the treatment is PVA / AgNO3-X, wherein X represents the proportion of AgNO3 in the total weight of PVA and AgNO3.
2. The preparation of the degradable antibacterial fiber material according to claim 1, characterized in that: Step (1) Preparation of silver nitrate Add distilled water to dilute analytical pure nitric acid HNO4, slowly add the crushed silver flakes to the diluted nitric acid, wait for it to slowly dissolve and then heat it up. After the yellow ammonia oxide disappears, evaporate and concentrate the dissolved supernatant until a white film appears on the surface of the container, then cool it to room temperature to obtain silver nitrate crystals; add the mixed solution containing the silver nitrate crystals to a suction filtration tank, vacuum filter, then wash with ice water, combine the filtrate and the washing water, and then concentrate and crystallize them again. The crystals are then dissolved in water and crystallized to obtain high-purity AgNO3; Step (2) Preparation of PVA / AgNO3 composite foam PVA powder is poured into the AgNO3 solution prepared in step (1), stirred, and then placed in a sealed container to fully plasticize the solution; the plasticized particles are subjected to hot pressing to obtain PVA / AgNO3 composite sheets, and the composite material obtained after the treatment is PVA / AgNO3-X, wherein X represents the proportion of AgNO3 in the total weight of PVA and AgNO3; in order to ensure that there is enough silver to form a network structure during the low-temperature in-situ solid-phase reaction stage and to prevent PVA from being over-plasticized and the melting decomposition temperature from being too low, the value of X is set within a certain range; Step (3) Preparation of silver foam by low-temperature in-situ solid phase reaction The PVA / AgNO3 composite foam prepared in step (2) is placed in a muffle furnace, and after heating, an in-situ solid phase reaction is induced to obtain a metallic silver foam; Step (4) Preparation of chitosan spinning solution Dissolve corn starch in distilled water and place in a high-pressure steam sterilizer to completely gelatinize it; cool the gelatinized starch, add pullulanase to perform enzymatic debranching, inactivate the enzyme, and cool to room temperature to obtain a debranched corn starch solution (DBS); add the silver foam prepared in step (3) and an acetic acid solution to obtain a chitosan spinning solution; Step (5) Chitosan microcapsule The chitosan spinning solution prepared in step (4) is added to folic acid, and sheared to obtain a wall core material suspension containing folic acid, and then spray-dried at the inlet to obtain chitosan-folic acid microcapsules; Step (6) Preparation of CS / CNC sheath-core fiber Connect a syringe containing chitosan solution to the outer diameter of the coaxial needle, connect a syringe containing CNCs (cellulose nanocrystals) suspension to the inner diameter of the needle, and place both syringes on a syringe pump, inject them into a coagulation bath and add the chitosan microcapsules prepared in step (5) to obtain CS / CNC skin-core fibers; the coagulation bath is a mixture of sodium hydroxide solution and ethanol; Step (7) Preparation of biodegradable antibacterial fiber material The CS / CNC sheath-core fiber prepared in step (6) is added, and CA (carbonate) is dissolved in a mixed solvent of acetone and deionized water to prepare a polymer / solvent / non-solvent precursor solution, and then the precursor solution is coated on different fabrics using a doctor blade coater, and then allowed to stand in a high humidity environment; the obtained hierarchical micro-nano porous CA / CS / CNC fiber network coating is placed in a vacuum oven to completely dry to remove acetone and water; after drying, the independent CA / CS / CNC coating is peeled off.
3. The preparation of a degradable antibacterial fiber material according to claim 2, characterized in that: Step (1) Preparation of silver nitrate Analytical pure nitric acid HNO4 is diluted with distilled water 1-2 times at a ratio of 1-5:1-2, and the crushed silver flakes are slowly added to the diluted nitric acid at a ratio of liquid:solid=1-2.5:1-3, and dissolved at room temperature. After the dissolution is slow, the temperature is raised to 80-90°C. After the yellow ammonia oxide disappears, the dissolved supernatant is heated to 80-90°C, evaporated and concentrated until a white film appears on the surface of the container, and then cooled to room temperature to obtain silver nitrate crystals; the mixed solution containing the silver nitrate crystals is added to a suction filtration tank, vacuum filtered, and then washed with ice water 1-2 times to produce silver nitrate crystals with a purity greater than 90-99.8%; the filtrate and washing water are combined, concentrated and crystallized for a second time, and the crystals are then dissolved in water and crystallized to obtain AgNO3 with a purity of more than 90-99.5%.
4. The preparation of a degradable antibacterial fiber material according to claim 3, characterized in that: Step (2) Preparation of PVA / AgNO3 composite foam PVA powder is poured into the AgNO3 solution prepared in step (1), stirred for 10-15 minutes, and then placed in a sealed container and allowed to stand at 35-40°C for 40-48 hours to fully plasticize the solution; the plasticized particles are subjected to hot pressing to obtain PVA / AgNO3 composite sheets with a thickness of 2.0-4.0 mm; the molding temperature is 100-150°C and the molding pressure is 10-15.0 MPa; the obtained composite material is PVA / AgNO3-X, wherein X represents the proportion of AgNO3 in the total weight of PVA and AgNO3; in order to ensure that there is sufficient silver to form a network structure during the low-temperature in-situ solid-phase reaction stage and to prevent PVA from being over-plasticized and the melting decomposition temperature from being too low, the value of X is set to 10-50.
5. The preparation of a degradable antibacterial fiber material according to claim 4, characterized in that: Step (3) Preparation of silver foam by low-temperature in-situ solid phase reaction The PVA / AgNO3 composite foam prepared in step (2) is placed in a muffle furnace and heated to 160-210°C at a heating rate of 1-5°C / min to induce an in-situ solid phase reaction to obtain metallic silver foam.
6. The preparation of a degradable antibacterial fiber material according to claim 5, characterized in that: Step (4) Preparation of chitosan spinning solution Dissolve 10-15 g corn starch in 90-100 mL distilled water, place in a 100-121° C. high pressure steam sterilizer for 15-20 min to completely gelatinize it; cool the gelatinized starch to 50-58° C., add 180-200 μL pullulanase for enzymatic debranching for 1-5 h, inactivate the enzyme, and cool to room temperature to obtain a debranched corn starch solution (DBS); add the silver foam prepared in step (3), and add 1-3% acetic acid solution to prepare a chitosan spinning solution with a mass fraction of 0-2%.
7. The preparation of a degradable antibacterial fiber material according to claim 6, characterized in that: Step (5) Chitosan microcapsule The chitosan spinning solution prepared in step (4) is added to folic acid, and sheared at 6000-6500 r / min for 15-30 min to obtain a wall core material suspension containing 0.5-2% folic acid, and then spray-dried at an inlet temperature of 150-200° C. and a flow rate of 1-4 mL / min to obtain chitosan-folic acid microcapsules.
8. The preparation of a degradable antibacterial fiber material according to claim 7, characterized in that: Step (6) Preparation of CS / CNC sheath-core fiber A 10-15 mL syringe filled with 2.0-2.5% chitosan solution is connected to the outer diameter of a coaxial needle (needle inner diameter 0.30-0.50 mm, needle outer diameter 1.20-1.26 mm), a 1-5 mL syringe filled with CNCs suspension (0-4%) is connected to the inner diameter of the needle, and both syringes are placed on a syringe pump, injected into a coagulation bath at a flow rate of 0.6-0.8 mL / min and the chitosan microcapsules prepared in step (5) are added to obtain CS / CNC skin-core fibers; the coagulation bath is a mixture of 1-5% sodium hydroxide solution and ethanol, wherein the mass ratio of sodium hydroxide solution to ethanol is 3-6:2-4.
9. The preparation of a degradable antibacterial fiber material according to claim 8, characterized in that: Step (7) Preparation of biodegradable antibacterial fiber material The CS / CNC sheath-core fiber prepared in step (6) is added, and CA is dissolved in a mixed solvent of acetone and deionized water to prepare a polymer / solvent / non-solvent precursor solution; the precursor solution is then coated on the fabric using a blade coater, and then allowed to stand for 1-5 hours at room temperature of 20-25°C and a high humidity environment of 90-95%; the obtained hierarchical micro-nano porous CA / CS / CNC fiber network coating is placed in a vacuum oven to completely dry to remove acetone and water; after drying, an independent CA / CS / CNC coating is peeled off, and the coating maintains the same thickness, the coating on the fabric is about 45-50µm, and the independent coating is about 95-100µm.
Citation Information
Patent Citations
Antibacterial medical dressing film carrying nano-silver and cellulose nanocrystalline hybrid materials and preparation method thereof
CN104153120A
Preparation method of nano silver chloride / chitosan fiber anti-bacterial dressing
CN104324407A
Preparation method of silver-chitosan composite antibacterial material
CN108902179A
Preparation method of nano-silver / cellulose composite antibacterial material
CN111995799A
Antibacterial microcapsule, preparation method thereof, long-acting antibacterial dressing and application
CN116019962A